Rev-RRE activity modulates HIV-1 replication and latency reactivation: Implications for viral persistence and cure strategies. - Godfrey A Dzhivhuho; Patrick E H Jackson; Ethan S Honeycutt; Flavio da Silva Mesquita; Jing Huang; Marie-Louise Hammarskjold; David Rekosh (PLoS Pathogens)
The HIV-1 Rev-RRE regulatory axis plays a crucial role in viral replication by facilitating the nucleo-cytoplasmic export and expression of viral mRNAs with retained introns. In this study, we investigated the impact of variation in Rev-RRE functional activity on HIV-1 replication kinetics and reactivation from latency. Using a novel HIV-1 viral vector with an interchangeable Rev cassette, we engineered viruses with two diverse Rev functional activities and demonstrated that higher Rev-RRE activity confers greater viral replication capacity while maintaining a constant level of Nef expression. In addition, a low Rev activity virus rapidly acquired a compensatory mutation in the RRE that significantly increased Rev-RRE activity and replication. In a latency model, proviruses with differing Rev-RRE activity levels varied in the efficiency of viral reactivation, affecting both initial viral release and subsequent replication kinetics. These results demonstrate that activity differences in the Rev-RRE axis among different viral isolates have important implications for HIV replication dynamics and persistence. Importantly, our findings indicate that bolstering Rev/RRE activity could be explored as part of latency reversal strategies in HIV cure efforts.